View of the colonnade on the main entrance of the Matha - Temples of India Project Team (Jio Institute, 2024)
Pictured here is a view of the colonnade on the left side of the main entrance of the matha (monastic or residential building) of the Suhaveshwar Temple. A row of pillars divides the space into horizontal bays. The front bay leads into two small rooms, one each at the end of the hall. The second connects to different enclosed spaces that are placed equidistantly and connected to the back wall of the matha. The enclosed rooms that are connected to the front bay are entered through an ornate dvarashakha (architrave).